Evaluation of Fibrosis Markers: Apelin and Transforming Growth Factor-β1 in Autosomal Dominant Polycystic Kidney Disease Patients - Kocer, Derya; Karakukcu, Cigdem; Ozturk, Fahir; Eroglu, Eray; Kocyigit, Ismail (Therapeutic apheresis and dialysis, 2016)
Renal interstitial fibrosis is an important pathological feature of autosomal dominant polycystic kidney disease (ADPKD), which progressively develops to end‐stage renal disease (ESRD). It has been shown that apelin and transforming growth factor‐β1 (TGF‐β1) play important roles in the renal fibrosis process. The aim of the present study is to evaluate the relationship of these fibrosis markers and ADPKD. Forty‐five patients with ADPKD and 28 healthy controls were studied cross‐sectionally. Estimated glomerular filtration rate (eGFR), apelin, TGF‐β1 were measured in all participants, using conventional methods. Apelin levels were lower (1.2 ± 0.9 ng/mL vs. 2.5 ±  1.3 ng/mL, P < 0.001), while TGF‐β1 levels were higher in the patient group according to healthy controls (466.5 ±  200.5 ng/L vs. 367.1 ± 163.45 ng/L, P = 0.031), respectively. Apelin was negatively correlated with TGF‐β1 and highly sensitive C‐reactive protein (hs‐CRP); and positively correlated with eGFR. In all subjects, eGFR was independently predicted by TGF‐β1 and apelin. Apelin and TGF‐β1 may be used as biomarkers of renal fibrosis that is an important pathological feature of ADPKD, which progressively develops to ESRD in ADPKD patients.